Breaking Boundaries: A Comparative Analysis of Weak vs. Strong Bases in Eugenol Isolation from Syzygium aromaticum (L.) Merr. & LM Perry - Handayani, Dwi; Sitindaon, Rina SE; Hidayati, Nurul; Setiawansyah, Arif (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2023)
Eugenol, a phenolic compound classified within the phenylpropanoid group, stands out as a key constituent of clove oil, boasting a myriad of biological activities. Its isolation typically involves the utilization of an alkaline solution, yet the choice of alkaline agent significantly impacts the yield of eugenol. This study delves into the impact of various alkaline solutions on the isolated eugenol content from Syzygium aromaticum essential oil, leveraging its acidic properties to form a soluble eugenol salt in an aqueous medium. Employing alkaline solutions with a concentration of 1 N, including both strong bases (such as KOH, NaOH, and Ba(OH)₂) and weak bases (like Ni(OH)₂, Al(OH)₃, and Zn(OH)₂), we scrutinized the diverse outcomes on eugenol content. Results revealed that KOH yielded the highest eugenol content at 96.91%, while Zn(OH)₂ displayed the lowest at 20.99%. Nevertheless, the potential of weak alkaline solutions in the eugenol isolation process from Syzygium aromaticum essential oil remains noteworthy. Future endeavors should focus on optimizing the ideal concentration of weak alkaline solutions for this purpose.